Implication of Cytotoxic Helicobacter pylori Infection in Autoimmune Diabetes - Alessandro P. Delitala; Giovanni M. Pes; Hoda M. Malaty; Gavino Pisanu; Giuseppe Delitala; Maria P. Dore (Journal of Diabetes Research)
Background. Type 1 diabetes (T1D) and type 2 diabetes (T2D) have been linked to Helicobacter pylori infection, although results are conflicting. No previous study addressed a possible link between H. pylori infection and latent autoimmune diabetes in adults (LADA). In this study, a correlation among H. pylori infection and the risk of autoimmune diabetes in comparison with T2D was investigated. Methods. Sera from 234 LADA patients, 105 patients with late-onset T1D, and 156 patients with T2D were analyzed for anti-H. pylori and the cytotoxin-associated antigen (CagA) IgG antibodies. Results. H. pylori seroprevalence was comparable in LADA (52%), late-onset T1D (45%), and T2D (49%) with no gender differences. The seroprevalence of CagA IgG was significantly higher in autoimmune diabetes (late-onset T1D: 45%, LADA: 40%) compared to T2D (25%; p<0.028). Conclusions. Although H. pylori seroprevalence was similar in LADA, T1D, and T2D, anti-CagA positivity was significantly increased among patients with autoimmune diabetes, suggesting that more virulent H. pylori strains might be a trigger for immune mechanisms involved in their pathogenesis.